Active push deployment technique improves stent/vessel-wall interaction in endovascular treatment of acute stroke with stent retrievers. (14th March 2016) - Wiesmann, Martin; Brockmann, Marc-Alexander; Heringer, Sarah; Müller, Marguerite; Reich, Arno; Nikoubashman, Omid
Abstract : Background: The optimal interaction between stent struts and thrombus is crucial for successful revascularization in endovascular stroke therapy with stent retrievers. Deploying the stent retriever by actively pushing it into the thrombus increases the radial force with which the stent struts expand into the thrombus. Objective: To examine the active push deployment (APD) technique in an in vitro model and present our clinical experience with this technique. Methods: In an in vitro experiment we investigated the configuration of a Solitaire and a Trevo ProVue device (both 4×20 mm), depending on whether the devices were deployed using the APD technique or simple unsheathing. We retrospectively assessed the effectiveness and safety of this technique by analyzing 130 patients with large vessel occlusions (carotid T or M1 segment of the middle cerebral artery), who received endovascular treatment with a Trevo device (4×20 mm) that was deployed using the APD technique. Results: In vitro experiment: the APD technique improved apposition of the devices to the vessel wall. There was widening of 30% (Trevo) and 19% (Solitaire) at the cost of a shortening of 5% and 4%, respectively, when the devices were deployed in a carotid T model. Clinical study : the revascularization rate (Thrombolysis in Cerebral Infarction ≥2b) with the Trevo device was 90%. There were no retriever-associated dissections or perforations in 278 retrieval maneuvers. Conclusions: The APD technique improves apposition of the tested devices to the vessel wall. The widening effect comes at the cost of minimal shortening of the devices. Our clinical experience shows that using the APD technique to deploy the Trevo device is effective and safe.